Investigation of rheo-mechanical properties of cement suspensions activated in a hydrodynamic cavitator - Martyntsev, Volodymyr; Guzii, Sergii; Nazarenko, Ivan; Glyva, Valentyn; Guzii, Olena (Technology audit and production reserves, 2017)
The object of research is cement suspensions activated in a hydrodynamic cavitator. One of the most problematic places of the proposed method of activation is the slowing of the kinetics of the strength of astringents on days 2 and 7 of hardening. It is possible to speed up the set of strength by studying the processes of structure formation occurring in activated suspensions and hardening mixtures, and also to enhance physical effects by improving the design of the cavitator and the mixing chamber. During the study, activated water and 10 % cement-water suspension are used. After 10 minutes of cavitation treatment at pressures of 0.63–1.4 MPa and a temperature of 28–32 °C, the pH of the medium increases (pH+7.56) and decreases by a factor of 10.38 times the dynamic viscosity of the suspensions. This is due to the fact that the increase in pressure and temperature in the cement-water suspension contributes to the intensification of the dispersion of cement particles in the frequency range 700–800 Hz and the passage of intensive mass-transfer processes in the frequency range 1.9–3.5 kHz, leading to the formation of primary crystallization structures. Due to this, it is possible to obtain dilatant liquids with a viscosity of 160 to 273.5 cP and control the rate of agitation in the speed range from 50 to 200 min-1. Compared to similar activation methods, the approach under study provides an increase in brand strength of 1.14 times compared to an unactivated cement system and contributes to a decrease in the amount of Portland cement from 10 to 14 %.